The relationship between professional autonomy and job performance among Iranian ICU nurses: the mediating effect of job satisfaction and organizational commitment - Aysan Judi; Naser Parizad; Yousef Mohammadpour; Vahid Alinejad (BMC Nursing)
Abstract Background Although previous studies have linked professional autonomy to nurses’ job performance, research lacks how job satisfaction and organizational commitment mediate this relationship. Addressing this gap is essential for improving nursing practice outcomes. This study aims to determine the mediating effect of job satisfaction and organizational commitment in this relationship among Iranian nurses. Methods This descriptive-correlational study was conducted in Urmia teaching hospitals from October 2022 to June 2023. Four hundred twenty nurses were recruited using quota sampling. Eligible participants were selected non-randomly from predetermined numbers at four hospitals, and recruitment continued until the required sample size was achieved. Data were collected using demographic questionnaires, the Varjus Professional Autonomy Scale, the Porter Organizational Commitment Questionnaire, the Minnesota Satisfaction Questionnaire, and the Paterson Job Performance Questionnaire. Data were analyzed using SPSS ver. 23 and SmartPLS ver. 3. Results Professional autonomy had a positive, direct, and strong effect on nurses’ job performance (β = 0.708, t-value = 9.867, p < 0.001). Professional autonomy had a positive, direct, strong impact on job satisfaction (β = 0.854, t-value = 39.736, p < 0.001) and a positive, minor, and direct effect on organizational commitment (β = 0.199, t-value = 3.150, p = 0.000). Professional autonomy positively affects job performance through job satisfaction (β = 0.4016, 95% CI: 0.3280, 0.4736) and organizational commitment (β = 0.7582, 95% CI: 0.6088, 0.9086). Conclusions Healthcare managers should promote nurses’ autonomy and job satisfaction to enhance their performance. They can improve working conditions by offering competitive salaries, simplifying promotion processes, and involving nurses in decisions related to patient care. Additionally, essential steps to consider are supporting nursing autonomy, organizing educational classes, and implementing strategies such as stress reduction programs, reducing workloads, addressing nursing shortages, and decreasing working hours.